Lifetime Mental Health Problems in Adult Lower Secondary Education: A Student Survey - Aznárez-Sanado, Maite; Artuch-Garde, Raquel; Carrica-Ochoa, Sarah; García-Roda, Carlos; Arellano, Araceli; Ramírez-Castillo, David; Arrondo, Gonzalo (Frontiers in Psychology, 2020)
Background/objective: Adult Lower Secondary Education is an education program for basic qualifications for the labor market. Our study aimed to compare lifetime mental health problems between current Adult Lower Secondary Education students and higher Vocational Education students, as the former constitutes a highly distinct and understudied group. Method: Findings were based on a cross-sectional self-report survey. Lifetime relative odds of occurrence of mental disorders (i.e., psychiatric disorders typically diagnosed in adults, learning difficulties or deficit hyperactivity disorder (ADHD)) were compared between Adult Lower Secondary Education students (n = 134) and Vocational Education students (n = 149). Results: While the frequency of mental health problems was high in both groups, psychiatric disorders typically diagnosed in adults were more common in Adult Lower Secondary Education students than among other students. Vocational Education students reported higher rates of ADHD. Conclusion: There is a need for additional psychological resources for Adult Lower Secondary Education students, an educational level that is the last path for many to acquire a basic degree.